Divine violence. Around René Girard’s scapegoat - Wiończyk, Grzegorz (Hybris, 2014)
Girard indicates an ancient text which we perfectly know as one of the books of the Holy Scripture - the Book of Job. He presents the ominous face of the sacred, the idea of a divinity, in the name of which a scapegoat can be selected and executed. Job for Girard is an unsuccessful scapegoat, i.e. the one that has not accepted his fault. Had Job not rebel against the social intentions, today he would be an example of another subject of collective violence which brought unity to its community. The theory of Girard, who is of the opinion that each culture is based on founding murder and secondary sacralisation of the victim is particularly popular today, in the age of the problem of terrorism. Slavoj Žižek, commenting Benjamin, takes up this thread we are interested in. This theological dimension is divine violence, understood as intervention of a transcendent justice. Such an interpretation of religiously motivated terrorism is so far from Benjamin’s divine justice, that Žižek does not continue this thread. However, the person who does this is Płuciennik, who stresses that terrorists’ motivation has iconoclastic dimension. He notices that there is a strong current in the contemporary intellectual landscape, which refers to apocalyptic thinking, connected with retribution theology.